Quadrant-Based Analysis of Gross Enrollment Rate (GER) and Net Enrollment Rate (NER) for Mapping Educational Participation in North Sumatra Province, Indonesia (2020–2024) - Nurhidayah, Kartini; Nurdin, Diding; Suharto, Nugraha; Kurniatun, Taufani C; Affandi, Nurdin (Universitas Nurul Jadid, 2026)
This study aims to analyze educational participation in North Sumatra Province at the primary, junior secondary, and senior secondary education levels during the period of 2020–2024 based on the indicators of Gross Enrollment Rate (GER) and Net Enrollment Rate (NER). The study employed a descriptive quantitative approach using a quadrant-based analysis method. Secondary data were obtained from the Central Statistics Agency (BPS) of Indonesia and analyzed by comparing the GER and NER of North Sumatra Province with national average indicators at each educational level and year of observation. The findings reveal that primary education consistently falls into Quadrant I (high GER and high NER), indicating broad and age-appropriate educational participation. Junior secondary education tends to fall into Quadrant III (relatively lower GER and high NER), reflecting effective participation among students within the ideal school-age group despite relatively limited overall access. Meanwhile, senior secondary education is categorized into Quadrant II (high GER and low NER), indicating age-grade distortion and delayed educational participation. The study concludes that educational participation at the primary level in North Sumatra has been relatively equitable and effective, while challenges remain at the secondary level, particularly regarding age-appropriate participation and continuity of educational access. These findings imply the importance of quadrant-based educational policies to improve equitable, inclusive, and sustainable educational participation.